Answer:
The constant would be A) 9
Step-by-step explanation:
The Constant in a math expression is One number that is on its own or without a varialbe
Answer:
2(x-3)(x-1)
Step-by-step explanation:
2(x+x+3)
2(x-3)(x-1)
Hope this will help u....
1. C - You could add 6 and divide by negative three with this one
2. B - By plugging in five, you would get 9-10. and that would give you -1
3. B - You would add 18 to 12 to get 30
Answer:
Hey Dude ok so it's g = 7 Have a nice day!
Step-by-step explanation:Simplifying
-2 = g + -9
Reorder the terms:
-2 = -9 + g
Solving
-2 = -9 + g
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '-1g' to each side of the equation.
-2 + -1g = -9 + g + -1g
Combine like terms: g + -1g = 0
-2 + -1g = -9 + 0
-2 + -1g = -9
Add '2' to each side of the equation.
-2 + 2 + -1g = -9 + 2
Combine like terms: -2 + 2 = 0
0 + -1g = -9 + 2
-1g = -9 + 2
Combine like terms: -9 + 2 = -7
-1g = -7
Divide each side by '-1'.
g = 7
Simplifying
g = 7